The Indonesia's Strategies For Exclusive Economic Zone (EEZ) Sovereignty With 1982 UNCLOS Provisions: North Natuna Sea - Budi Pramono (Lembaga Kajian Pertahanan Strategis, 2023)
North Natuna Sea's abundance of natural resources provides a tremendous pull for diverse parties, who, for the sake of profit maximization, are willing to commit any crime. A further report found that the claims of South East Asean countries and China on Indonesia's Exclusive Economic Zone (EEZ) waters in North Natuna Sea are completely divorced from the attractiveness of the natural resources. Considering the strategies to resolve any differences and the disputes between South East Asean countries and China in a peaceful manner through dialogue, affirming commitment to the goals and principles of UNCLOS, 1982, this paper provides a systematic review of the strategies as a the treaty of amity and cooperation in the South East Asian model for Indonesia’s stability which promotes agency and reflective practice. Comparing the current practice of the current waters’ cases in North Natuna Sea to the international stabilities reported in the literature, this review suggests that North Natuna Sea needs adopt two strategies that are concurrently executed and mutually supportive. The first is a diplomatic strategy consisting of two simultaneous steps, the first of which involves efforts to expedite the implementation of negotiations and the conclusion of a territorial boundary agreement between Indonesia and the Philippines, India, Malaysia, Palau, Singapore, Thailand, Timor-Leste, and Vietnam. sea. The second strategy is a defense diplomacy approach to China, by leveraging Indonesia-China bilateral defense cooperation and multilateral defense cooperation venues such as ARF and ADMM Plus where China is a discussion partner. Key words: Indonesia, Exclusive Economic Zone (EEZ), Sovereignty, 1982 UNCLOS Provisions, North Natuna Sea